Observer's Guide to Variable Stars - Griffiths, Martin (The Patrick Moore Practical Astronomy Series,, 2018)
This book contains everything you need to know about variable stars -- stars whose brightness varies noticeably over time. The study of variable stars has been a particularly popular area of research for amateurs for many years; the material contained herein serves as both an introduction to amateur astronomers and a useful reference source for seasoned variable star observers. With its thorough, non-mathematical descriptions of variable stars and tips for how to see them, this book enables novices and experts alike to set off into the field and observe a wide range of delightful sights. It strikes a balance between easily visible objects that can be seen in any telescope or binoculars, and variable stars that are a direct challenge to those with large aperture equipment or access to photometric tools and methods. After helping the observer differentiate between variable star types, the author goes on to explain the skills needed to operate a telescope and other equipment, as well as how to couple filters to a CCD camera or digital SLR camera in order to photometrically record these celestial objects. Further, the book includes an observational guide to 50 objects for study, with finder charts and data about light curves for ease of identification, along with the stars' celestial coordinates, magnitudes, and other pertinent information.